1996
DOI: 10.1523/jneurosci.16-02-00649.1996
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of sensory cells after laser ablation in the lateral line system: hair cell lineage and macrophage behavior revealed by time- lapse video microscopy

Abstract: The regeneration of sensory hair cells in lateral line neuromasts of axolotls was investigated via nearly continuous time-lapse microscopic observation after all preexisting hair cells were killed by a laser microbeam. The laser treatments left neuromasts with one resident cell type, which was supporting cells. Over the course of 1 week, replacement hair cells arose either directly via differentiation of cells present in the epithelium from the beginning of the time-lapse period or via the development of cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 54 publications
4
128
1
Order By: Relevance
“…1993; Warchol et al 1993;Kelley et al 1995;Fekete 1996;Jones & Corwin 1996). During the ¢nal mitotic divisions, which occur in the mouse at E12^E14, pluripotent progenitors give rise to non-sensory precursors (NSP) and prosensory precursors (PSP).…”
Section: Immortalized Auditory Hair Cell Precursors M N Rivolta Andmentioning
confidence: 99%
“…1993; Warchol et al 1993;Kelley et al 1995;Fekete 1996;Jones & Corwin 1996). During the ¢nal mitotic divisions, which occur in the mouse at E12^E14, pluripotent progenitors give rise to non-sensory precursors (NSP) and prosensory precursors (PSP).…”
Section: Immortalized Auditory Hair Cell Precursors M N Rivolta Andmentioning
confidence: 99%
“…The supporting cells then migrate through the sensory epithelium and regenerate by cell division (i.e., mitosis) [7,. During mitosis, one or more daughter hair cells are generated either through symmetrical differentiation, which produces two hair cells or two supporting cells [18,24,41], or asymmetrical differentiation that produces one hair cell and one supporting cell (Figure 2(a)) [27,31,38,41]. Alternatively, hair cells might convert or transdifferentiate from neighboring supporting cells through nonmitotic mechanisms (Figure 2(b)) [33,[51][52][53][54][55].…”
Section: Supporting Cell Proliferation or Transdifferentiation: Whichmentioning
confidence: 99%
“…Resident macrophages recognize and destroy dying cells by engulfing them [58] and many secrete substances that may influence cell function [59]. Although the functional role of macrophages in the inner ear is unknown, numerous studies have demonstrated that macrophages and leukocytes reside in the undamaged sensory epithelia of the inner ear and are recruited to traumatized areas prior to the initiation of supporting cell proliferation [31,45,56,[60][61][62][63][64][65].…”
Section: Growth Factors and Immune Response Following Traumamentioning
confidence: 99%
“…New hair cells can be generated during adult life in fish, amphibians and birds (but unfortunately not in the mammalian cochlea). Support cells can divide and form new hair cells (Jones and Corwin, 1996;Fekete et al, 1998;Lang and Fekete, 2001). The pattern of division and differentiation is not fixed, however, and a support cell can produce two support cells or one hair cell and one support cell.…”
Section: Lineage Relationshipsmentioning
confidence: 99%